Adaptability of Miscanthus Cultivars for Biomass Production - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
In 2014, miscanthus dry matter (DM) did not differ between cultivars, averaging 10,970 lb/a. Total two-year production totaled 15,920 lb DM/a.
Keywords: bioenergy crop; dry matter; establishment